Building brand loyalty through user engagement in online brand communities in social networking sites. Issue 1 (2nd March 2015) - Zheng, Xiabing; Cheung, Christy M. K.; Lee, Matthew K.O.; Liang, Liang
Abstract : Purpose: – The purpose of this paper is to explore the concept of user engagement in the context of online brand communities. A research model is proposed to explain how brand loyalty is developed through user engagement. Design/methodology/approach: – The research model was empirically tested with an online survey study of 185 current Facebook users. Findings: – Results revealed that user engagement influenced brand loyalty both directly and indirectly through online community commitment. Users tend to focus on the benefits (rather than the costs) derived from the usage when they engage in an online brand community. Research limitations/implications: – The selection of respondents is bound to the Hong Kong area, while Facebook members are globally distributed. In addition, this study involved a cross-sectional design instead of investigating the development of brand loyalty from a long-term perspective. Practical implications: – The results inform e-marketers the importance of user engagement behaviors for building brand loyalty through online communities. Strategies that encourage members to engage in online brand communities on social networking sites such as Facebook are also provided. Originality/value: – The concept of user engagement in online brand communities is still poorly understood, underscoring the need for theoretically based research of user engagement. This paper enriches the knowledge in the area of brand engagement by presenting a research model that introduces the concept of user engagement in social media research and empirically examines its role in building brand loyalty in online brand communities.